2000
DOI: 10.1139/f00-004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution shifts and overfishing the northern cod (Gadus morhua): a view from the ocean

Abstract: Research on northern cod (Gadus morhua) from 1983 to 1994 indicated that a southward shift in distribution in the early 1990s was real and not an artifact of sequentially fishing down local populations. In the early 1990s, seasonal fishery and survey data showed distribution changes where there was no fishery, and large tonnage and densities (450 000 t, densities fourfold higher than 1980s levels) appeared in the south concurrent with declines in the north. All fishery, acoustic, and trawl survey indices incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 42 publications
4
98
2
1
Order By: Relevance
“…While boreal plankton have been shifting further south in the Northwest Atlantic (Johns et al 2001, Reid et al 2007), the opposite pattern has been observed in the Northeast Atlantic, with subtropical and temperate plankton shifting further north by as much as 1000 km during the past four decades . Comparable southward shifts by boreal fish species in Northwest Atlantic (Rose et al 2000, Vilhja´lmsson et al 2005 and northward shifts by subtropical and temperate fish species in the Northeast Atlantic have also been observed (Perry et al 2005, Vilhja´lmsson et al 2005). Reid and Beaugrand (2002) provide a more complete discussion of the relationship between these shifts in distributional patterns and the hydrometeorological processes driving them.…”
Section: Biogeographic Range Expansions Of Boreal Planktonmentioning
confidence: 91%
See 1 more Smart Citation
“…While boreal plankton have been shifting further south in the Northwest Atlantic (Johns et al 2001, Reid et al 2007), the opposite pattern has been observed in the Northeast Atlantic, with subtropical and temperate plankton shifting further north by as much as 1000 km during the past four decades . Comparable southward shifts by boreal fish species in Northwest Atlantic (Rose et al 2000, Vilhja´lmsson et al 2005 and northward shifts by subtropical and temperate fish species in the Northeast Atlantic have also been observed (Perry et al 2005, Vilhja´lmsson et al 2005). Reid and Beaugrand (2002) provide a more complete discussion of the relationship between these shifts in distributional patterns and the hydrometeorological processes driving them.…”
Section: Biogeographic Range Expansions Of Boreal Planktonmentioning
confidence: 91%
“…Relative to the 1980s, cod stocks collapsed during the early 1990s. Although overfishing was the predominant cause of this collapse, the cold, low-salinity Arctic waters entering the northern portion of their range from the Canadian Archipelago have hampered the subsequent recovery of cod (Rose et al 2000, Vilhja´lmsson et al 2005. Other species of fish and crustaceans have increased in abundance during this period (Frank et al 2005, Pershing et al 2005, Vilhja´lmsson et al 2005.…”
Section: Regime Shift In the Northwest Atlanticmentioning
confidence: 99%
“…truncated age/size classes) and thereby weakens the remaining population's capacity to buffer the effects of unfavorable environmental conditions . Also, climateinduced spatial contractions or merging of exploited fish stocks can lead to increases in local fish densities and catchability, which in turn make stocks more vulnerable to overfishing (Atkinson et al 1997, Rose et al 2000. These effects are very dependent on the life history adaptations that species or stocks have evolved to deal with environmental variability, predation pressure and onto genetic division of prey resources.…”
Section: Conservationmentioning
confidence: 99%
“…These cod would remain along the coastline during the summer to feed primarily on capelin, and then would migrate back offshore to overwinter and spawn the following spring. With the severe decline in the abundance of cod offshore, large schools of northern cod no longer move along the migration pathways (Rose et al, 2000). However, a 'Sentinel Fishery' for cod established by DFO to monitor traditional inshore fishing grounds provides evidence that cod still migrate to the Labrador coast to feed (Lilly et al, 2004).…”
Section: Shelf-spawning Species For Which Gilbert Bay Is a Nursery Areamentioning
confidence: 99%